$\text{Er}^{3+}$ - Doped Nanoengineered Yttria-Stabilized Zirconia Alumino-Silicate Fiber for Efficient CW and Mode-Locked Laser Operation - Y. W. Lee; J. S. Chang; S. Das; A. Dhar; M. Pal; M. C. Paul; J. T. Lin; Y. W. Jhang (IEEE Photonics Journal, 2016)
We report on the development of efficient continuous wave (CW) and mode-locked ring fiber lasers utilizing an $\text{Er}^{3+}$ - doped nanoengineered yttria-stabilized zirconia alumino (YSZA)-silicate fiber as the gain element. With the proper design of the material composition, the YSZA fiber host presents superior features to eliminate the $\text{Er}^{3+}$ cluster effects and enhance the radiative emission over commercial silica fibers, thus significantly increasing the fiber laser efficiencies. Through cavity analysis and optimization, we successfully demonstrate a 975-nm pumped single-mode $\text{Er}^{3+}$ - doped CW YSZA-silicate fiber laser with a slope efficiency of 43%, which is corresponding to the quantum efficiency of 69%. Because of the special dispersion property of the $\text{Er}^{3+}$ - doped YSZA-silicate fiber, we are able to build a stable soliton mode-locked 1565-nm fiber laser with 3.2-nJ pulse energy, 644-fs pulsewidth, and 4.96-kW peak power.